Do changing institutional settings matter? Educational attainment and family related employment interruptions in Germany - Drasch, Katrin; Wiemers, Jürgen (Nürnberg, 2011)
"Cross-sectional studies show that in West Germany women with different levels of educational attainment participate differently in the labor market. In this paper, I examine one potential underlying mechanism: the re-entry of mothers in the labor market after a period of inactivity. I argue that besides societal changes the reforms of parental leave legislation could be responsible for the educational divide in mothers' employment. Hypotheses are derived from human capital theory and labor supply theory assuming a rational behavior of women. Using retrospective life-course data from the IAB study ALWA, I find evidence that women with different levels of educational attainment have different re-entry patterns also when taking the educational attainment of the partner into account. Furthermore, parental leave schemes play a crucial role for re-entries. Some evidence of an educational polarization of re-entry behavior is found after the year 2000."